Migrant workers and socio-economic changes - Joko Sayono; Indah Wahyu Puji Utami; Lutfiah Ayundasari (Faculty of Social and Political Science, Universitas Airlangga, 2018)
This study was conducted based on the socio-economic changes among South Malang’s residents due to the recognition of a new job opportunity, namely the role of migrant worker. The objective of this study is to describe the socio-economic changes in South Malang from a historical standpoint from the 1980s to 2015. In the 1980s, being a migrant worker as a job opportunity was popular, but in 2015, the number of migrant workers started to decrease drastically due to the changing of the economic direction. This study was conducted in eleven sub-districts in South Malang, which is known as the origin place of migrants, and where many of the residents have worked as migrant workers. The data used in this study was collected by interviewing and tracking the archives of the social economic development of the Malang District by way of various institutions. The results of this study indicate that the South Malang residents chose to work as migrant workers based on three main factors. First, are the internal factors that consist of the economic and infrastructure limitations. The external factor consist of the Oil Boom and Asian Miracle’s impact. Second, are the unproductive and costly environmental conditions which forced the residents to move out and find better life prospects. Third, is the socio-cultural context, where the society has only known about monetisation since the colonial era. The combination of these factors motivates the rural community of South Malang to work as migrant workers and this changed the socio-economic landscape of the region from plantations and subsistence agriculture to having a capitalist focus in the period 1980 to 2015. The positive impacts brought about by the presence of migrant workers in South Malang include economic progress, socio-economic welfare, and area improvement. On the other hand, the negative impacts include the increasing number of divorce cases, the cases of child abandonment, and the increase in the number of juvenile delinquency cases.